A phased approach to implementing the Breast Imaging Reporting and Data System (BI‐RADS) in low‐income and middle‐income countries. (29th April 2020) - Lam, Diana L.; Entezari, Pegah; Duggan, Catherine; Muyinda, Zeridah; Vasquez, Andres; Huayanay, Jorge; Anderson, Benjamin O.; Scheel, John R.
Abstract : Background: Successful breast cancer detection programs rely on standardized reporting and interpreting systems, such as the Breast Imaging Reporting and Data System (BI‐RADS), to improve system performance. In low‐income and middle‐income countries, evolving diagnostic programs have insufficient resources to either fully implement BI‐RADS or to periodically evaluate the program's performance, which is a necessary component of BI‐RADS. This leads to inconsistent breast ultrasound interpretation and a failure to improve performance. Methods: The authors applied the Breast Health Global Initiative's phased implementation strategy to implement diagnostic ultrasound and BI‐RADS within the context of a limited‐resource setting. Results: The authors recommended starting with triage ultrasound to distinguish suspicious masses from normal breast tissue and benign masses such as cysts because the majority of health workers performing ultrasounds at this level have minimal breast imaging experience. Transitioning to full diagnostic ultrasound with condensed or full BI‐RADS should occur after performance and quality metrics have been met. Conclusions: Transitioning through these phases across facilities likely will occur at different times, particularly in rural versus urban settings. Abstract : In the absence of adequate resource allocation, full Breast Imaging Reporting and Data System (BI‐RADS) implementation is not resource appropriate, leading to erroneous interpretations and the perpetuation of bad practices in breast cancer management. This article describes a phased strategy for implementing BI‐RADS in low‐income and middle‐income countries, adapting it for local resource levels and gradually adding to its complexity and usefulness as sonographer experience and infrastructure for monitoring patient outcomes advance.